2021
DOI: 10.3389/fvets.2021.756629
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Shegandilong Granule and Doxycycline on Immune Responses and Protection Against Avian Infectious Bronchitis Virus in Broilers

Abstract: Infectious bronchitis (IB) causes significant economic losses to commercial chicken farms due to the failures of vaccine immunization or incomplete protection. In this study, we evaluated the combination effect of Shegandilong (SGDL) granule (a traditional Chinese veterinary medicine) and doxycycline on the prevention of IBV infection and injury in the respiratory tract in broilers. A total of 126, 7-day-old broilers were randomly divided into four groups after vaccination. Group I served as a control. Broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…SARS-CoV-2 and IBV are highly infectious coronaviruses and leading causes of morbidity and mortality rates in infected hosts [53][54][55]. Currently, there are no effective methods or proven therapies to control the viral spread and mitigate disease progression for SARS-CoV-2 and IBV infections [56][57][58]. Furthermore, inherited mutagenic characteristics of SARS-CoV-2 and IBV limit the efficacy of available vaccines and exacerbate the disease situations [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 and IBV are highly infectious coronaviruses and leading causes of morbidity and mortality rates in infected hosts [53][54][55]. Currently, there are no effective methods or proven therapies to control the viral spread and mitigate disease progression for SARS-CoV-2 and IBV infections [56][57][58]. Furthermore, inherited mutagenic characteristics of SARS-CoV-2 and IBV limit the efficacy of available vaccines and exacerbate the disease situations [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Licl has been shown to suppress the inflammatory response induced by IBV by downregulating the inflammation-related genes NF-κB, NLRP3, TNF-α, and IL-1β ( Liu et al., 2022 ). The Chinese medicines Astragalus polysaccharide, forsythoside A, chlorogenic acid, Shegandilong Granule , and Doxycycline was found to modulate the inflammatory response induced by IBV by suppressing NF-κB expression and thus the expression levels of inflammatory factors ( Li et al., 2011 ; Zhang et al., 2017 ; Abaidullah et al., 2021 ; Feng et al., 2021 ). The present study showed that RIP could reduce the expression levels of the inflammatory factors IL-6, IL-8, and IL-1β by decreasing the expression levels of NF-κB, similar to previous studies ( Li et al., 2011 ; Feng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After infection, IgA is synthesized and transported through epithelial cells to the mucosal surface via a secretory component that neutralizes pathogens. As a result, the proliferation of pathogens is limited, but not completely inhibited, and serum IgA levels may be lower due to their secretion at the mucosal surface ( Ganapathy et al, 2005 ; Feng et al, 2021 ). Vaccination of 28-day-old turkeys with a subcutaneously injected inactivated vaccine against ORT had no influence on serum IgA levels, most likely because such vaccines usually induce systemic IgY-dependent immunity, whereas local immune responses involving IgA are limited.…”
Section: Discussionmentioning
confidence: 99%